2013
DOI: 10.2147/ijwh.s34030
|View full text |Cite
|
Sign up to set email alerts
|

Intravaginal rings as delivery systems for microbicides and multipurpose prevention technologies

Abstract: There is a renewed interest in delivering pharmaceutical products via intravaginal rings (IVRs). IVRs are flexible torus-shaped drug delivery systems that can be easily inserted and removed by the woman and that provide both sustained and controlled drug release, lasting for several weeks to several months. In terms of women’s health care products, it has been established that IVRs effectively deliver contraceptive steroids and steroids for the treatment of postmenopausal vaginal atrophy. A novel application f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 125 publications
0
63
0
5
Order By: Relevance
“…ntravaginal rings (IVRs) represent a promising approach to deliver anti-HIV microbicides with the premise to provide optimal drug concentrations for protection over a month or longer and to potentially improve adherence (1)(2)(3)(4)(5)(6)(7). Several IVRs are currently in different stages of development (5,8).…”
mentioning
confidence: 99%
“…ntravaginal rings (IVRs) represent a promising approach to deliver anti-HIV microbicides with the premise to provide optimal drug concentrations for protection over a month or longer and to potentially improve adherence (1)(2)(3)(4)(5)(6)(7). Several IVRs are currently in different stages of development (5,8).…”
mentioning
confidence: 99%
“…In comparison to gels and intravaginal films, IVRs currently provide the "gold standard" for sustained release and have been demonstrated to deliver contraceptives and provide long-term protection against STIs for over 90 days (80)(81)(82). The ASPIRE and IPM trials recently demonstrated the feasibility of dapivirine IVRs as PrEP against HIV, resulting in a decrease in the rate of HIV infection by 27% and 31%, respectively, for up to 1 month (83).…”
Section: Discussionmentioning
confidence: 99%
“…S obzirom da je rizik od neplanirane trudnoće istovremeno i rizik od infekcija prenosivih seksualnim putem, već dve decenije brojne organizacije, institucije od javnog značaja i farmaceutske kompanije, prevenstveno iz SAD, ulažu značajna finansijska sredstva za intenziviranje razvoja vaginalnih prstenova kao tehnologije za višenamensku prevenciju (Multipurpose prevention technologies, MPT) začeća i infekcija virusom humane imunodeficijencije (human immunodeficiency virus, HIV) i Herpes virusima [60]. Prema zvaničnom statističkom izveštaju iz 2015. godine ukupan broj inficiranih HIV-om na globalnom nivou iznosi 36,7 miliona, pri čemu je u poslednjih godinu dana broj povećan za oko 2,1 milion [61].…”
Section: Vaginalni Prstenovi Za Progestinsku Kontracepcijuunclassified
“…Prva faza kliničkih ispitivanja započela je 2015. godine. Od posebnog značaja je procena njegove pogodnosti da se oslobođenim tenofovirom ostvari antimikrobno delovanje u području primene, uz zanemarljivu sistemsku isporuku kako bi se smanjio rizik od razvoja rezistencije na antiretrovirotike, što je uobičajeno kada se primenjuju per os [60].…”
Section: Vaginalni Prstenovi Za Progestinsku Kontracepcijuunclassified